2017
DOI: 10.3390/app7030227
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Ti-6Al-4V Fabricated by Vertical Wire Feeding with Axisymmetric Multi-Laser Source

Abstract: Vertical wire feeding with an axisymmetric multi-laser source (feeding the wire vertically into the molten pool) has exhibited great advantages over LAM (laser additive manufacturing) with paraxial wire feeding, which has an anisotropic forming problem in different scanning directions. This paper investigates the forming ability of vertical wire feeding with an axisymmetric multi-laser source, and the microstructure and mechanical properties of the fabricated components. It has been found that vertical wire fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…It is noteworthy that the tensile properties reported for wire-fed laser deposited Ti6Al4V in the SRed condition (600°C, 4 hours) with orientations of D X and D Z included average UTS values of ∼975 MPa and ∼945 MPa, respectively, and average fracture strains of ∼4% and ∼8%, respectively [35]. For laser-deposited Ti6Al4V, the low fracture strains are a common problem [48] that may possibly be related to the martensitic microstructure and/ or gas shielding protection of the build. Also, previous research works on EBAM of Ti6Al4V have reported different values for the strength and ductility in the asdeposited condition; values for the UTS and total elongation have ranged from just under 800 MPa [20] to 925 MPa [18] and the total elongation from 9% [20] to 13% [18].…”
Section: Tensile Testingmentioning
confidence: 99%
“…It is noteworthy that the tensile properties reported for wire-fed laser deposited Ti6Al4V in the SRed condition (600°C, 4 hours) with orientations of D X and D Z included average UTS values of ∼975 MPa and ∼945 MPa, respectively, and average fracture strains of ∼4% and ∼8%, respectively [35]. For laser-deposited Ti6Al4V, the low fracture strains are a common problem [48] that may possibly be related to the martensitic microstructure and/ or gas shielding protection of the build. Also, previous research works on EBAM of Ti6Al4V have reported different values for the strength and ductility in the asdeposited condition; values for the UTS and total elongation have ranged from just under 800 MPa [20] to 925 MPa [18] and the total elongation from 9% [20] to 13% [18].…”
Section: Tensile Testingmentioning
confidence: 99%
“…Their difference lies in the lap way between layers and layers. The first and third tool-path schemes are the same for repeated scaninng, the difference is that one is mainly for the side wire feeding, one for the front and back feeding to testing the influence of the wire-feeding directions as shown in Figure 2a&c [12]. The layer is interlaced with the previous layer in the second tool-path scheme as show in Figure 2b.…”
Section: Methodsmentioning
confidence: 99%
“…Density functional theory (DFT) is the most widely used method to elucidate the structure of new materials and predict their electronic properties which have turned into enormous industrial endeavor . The chemistry of organic‐inorganic hybrid materials has attracted much attention as these materials demonstrate improved mechanical properties . Organic‐inorganic hybrid complexes of titanium(IV) find applications in the field of materials .…”
Section: Introductionmentioning
confidence: 99%